Romania : Financial Sector Assessment Program-Technical Note-Crisis Preparedness and Safety Net. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Note assesses the state of crisis preparedness and safety net in Romania. The bank resolution and crisis management toolkit has been significantly revamped since the last Financial Sector Assessment Program. The implementation of the Bank Resolution and Recovery Directive in Romania enhanced the National Bank of Romania's (NBR) powers to deal with failing banks, while the Bank Deposit Guarantee Fund gained greater involvement in these processes. The NBR has been charged with new responsibilities that flow from its ongoing role as supervisory and resolution authority, namely the enforcement and analysis of recovery planning requirements and the preparation of resolution plans. Some elements needed for the effectiveness to the crisis management framework are still work-in-progress.